(untitled) (Research, Society and Development, 2020)
Tomato fruits are excellent sources of antioxidants and nutrients for the human diet, tomato consumption has a great impact on nutrition and medicinal aspects. The objective of this study was to identify the irrigation water replacements and nitrogen doses that provide greater plant growth and productivity of sweet grape tomato fruits. The experimental design adopted was in randomized blocks, in a factorial scheme (4 x 4), with four replications. The factors were four nitrogen doses (50, 75, 100 and 125% of the recommended dose) and four water replacements (25, 50, 75 and 100% of the field capacity). The variables of plant height, stem diameter, leaf area and the SPAD index (Soil Plant Analysis Development) of the plants were evaluated, as well as the dry mass, soluble solids content and pH of the tomato fruits. Water replacement and nitrogen application significantly increase tomato plant growth and fruit quality. The maximum stem diameter and maximum leaf area were verified in water replenishment of 63.40 and 100%, respectively. The doses of N that favored the maximum dry mass were verified in the doses of 84.04%; 78.57% and 97.47% for water replenishment of 25%, 50% and 100% of field capacity. The nitrogen dose that favored a greater accumulation of dry matter in tomato fruits was at 84.04%; 78.57% and 97.47%, with a maximum dry matter of 9.45; 11.28 and 10.92 g, respectively. The application of 100% water replacement and 100% nitrogen dose influence the growth, development and quality of tomato fruits, promoting increases in crop productivity.